Ocfentanil testing in hair from a fatality case: Comparative analysis of a lock of hair versus a single hair fiber. (September 2021) - Allibe, N.; Paysant, F.; Willeman, T.; Stanke-Labesque, F.; Scolan, V.; Eysseric, H.
Highlights: Segmental single hair analysis compared with segmental hair lock analysis. Data on ocfentanil concentrations in hair in a fatality attributed to ocfentanil. Interest of complement hair testing to document ocfentanil–related death. Interpretation difficulties in hair testing. Abstract: In clinical and forensic toxicology, hair analysis offers a larger window for detecting drug exposure than blood or urine. Drug measurements are generally carried out using a segmented lock of hair, but few articles report the use of a single hair to document drug exposure. Nevertheless, single hair analysis can be very useful, particularly if only small amounts of biological matrices are available. More data on analyzing new synthetic opioids (NSOs) in hair are needed to help interpretation in future cases. In this study, segmental single hair analysis is compared with segmental hair lock analysis to document an ocfentanil-related death. The hair lock and single hair analyses were performed using the LC-MS/MS method after decontamination and incubation. Ocfentanil (OcF) concentrations ranged from 42 to 150 pg/mg in the segmented hair lock, depending on the segments. The hair lock and single hair analyses showed similar results: the highest concentrations were measured in the first two centimeters and decreased from root to tip. The similar profiles obtained from both the lock of hair and the single hair demonstrate the relevance of single hair analysis in cases where very few data are available. This article describes OcF concentrations in an authentic hair sample after a documented intake of this molecule in a fatality.